Tratamento físico-químico e cultivo de Desmodesmus subspicatus em vinhaça de cana-de-açúcar - Mattos, Luiz Felipe Arjonilla de (2014)
The traditional processes of biological dispollution of agro industrial waste water use aerobic and/or anaerobic systems, which generate biomass without commercial value and inevitable effluent nutrient losses. Alternatively, it s being studied the microalgae and cianobacteria application for a potential protein, lipid and other biomass constituent production for a minimization of the pollutant impact and as a way of valuating the residue. This way, heterotrophic cultivation of microalgae, is a proposal that could increase the viability of waste water treatment, once it uses organic compounds for the growth of this microorganisms in absence of light, being researched together with the bioremediation of effluents. Vinasse is a waste water highly produced in the fermentation-distillation process for the sugarcane based ethanol production. Depending on its biochemical composition in terms of organic matter and nutrients, the use of vinasse appears to be attractive as a substrate for biotechnological process development. Besides, physical-chemical treatments like pH adjusting and suspended solids flocculation must be studied for its use viabilization. D. subspicatus is a Chlorophyceae which has presented high cellular viability in cultivations using domestic and industrial waste water as substrate, easily tolerating temperature and pH variations. This said, this study aimed the the physicalchemical treatment of coagulation-flocculation and the heterotrophic cultivation of D. subspicatus in sugarcane vinasse aiming the biomass production. The results pointed that pH and aeration had low influence in the cultivation, and the ideal batch time is near 9 hours, lowering the effects of bacterial contamination. The physicalchemical treatment was able to remove COD at the maximum of 40% using calcium hydroxide and 60% using aluminum sulfate. The optimization of the process conditions raised the lipidic productivity from 69 to 244,8 mg.L-1.day-1, suggesting the viability of the heterotrophic cultivation of D. subspicatus in vinasse.